Kajian Peran Serta Masyarakat Untuk Mewujudkan Desa Plunturan Menjadi Desa Wisata Budaya - Mohammad Suyanto (Exchall: Economic Challenge, 2020)
Plunturan Village is located in Pulung sub-district, Ponorogo district. Plunturan Village is geographically a mountainous area that has a good view and also has the potential for culture and mores which are still preserved until now, so it is very possible to be developed into a cultural tourism village. Unique and interesting cultural potential and strong traditions from the community are one of the basic assets to build a cultural tourism village in order to increase community income. Tourism development that is oriented towards the potential of local wisdom is now starting to be favored by tourists, therefore the empowerment of the people of Plunturan Village through approaches and community awareness is needed so that they can use and have access to control in the development of cultural tourism villages, so that it is hoped that they can bring in many local tourists and abroad in order to improve the economy of the village community in Plunturan. The population of this study were all of the people of Plunturan Village who were involved in traditional and cultural activities in the village of Plunturan, while the research sample was determined by purposive sampling, by determining the number of research samples as many as 100 respondents. Data obtained from distributing questionnaires and field observations. Data analysis using qualitative descriptive analysis. The results showed that there was no management of tradition and culture as elements of cultural tourism villages, this was due to limited access, lack of knowledge and skills of the people of Plunturan Village, while in terms of natural potential as well as cultural wealth and traditions it was very supportive to be appointed as a cultural tourism village. When viewed from the point of view of the motivation and psychological readiness of the community based on the understanding of the principles of sustainability for tourism village development, it is very strong. Viewed from the government side, village policies are very supportive of the realization of a cultural tourism village, whereas from an institutional perspective, there are art and cultural studios. From the results of this study, it can be concluded that the village of Plunturan is very worthy of being appointed as a cultural tourism village. Key words: Plunturan Village, cultural tourism village